Evaluation of critical success factors for construction projects – an empirical study in Lithuania - Gudienė, Neringa; Banaitis, Audrius; Banaitienė, Nerija (International Journal of Strategic Property Management, 2013)
This paper aims to identify a comprehensive list of critical success factors for construction projects in Lithuania. Based on the available literature review, this paper identified 71 success factors under 7 broad groups. Based on the survey results, ten factors including project manager competence, project management team members’ competence, project manager coordinating skills, client clear and precise goals/objectives, project value, project management team members’ relevant past experience, project manager organising skills, project manager effective and timely conflict resolution, client ability to make timely decision, and project manager experience were determined as the most important success factors for construction projects. These critical success factors are of great significance both to researchers and industry practitioners. First Publish Online: 3 Apr 2013